Regional Cooperative Pollution Control and Residents' Health Expenditures: Empirical Evidence from China - Yuhui DAI; Zhidong TAN; Jianhua TAN; Lina YAN (Tehran University of Medical Sciences, 2019)
Background: Environmental pollution seriously damages not only the ecosystem but also the well-being of residents. There is an association between air pollution and residential health expenditures. The aim of this study was to identify the association between pollution control and residents' health expenditures. Methods: Using the pilot project of the regional cooperative pollution control in 28 cities required by the Chinese government as the quasi-natural experiment setting and the panel data of residents' health expenditures in China from 2014 to 2017, the impact of pollution control on residents' health expenditures was systematically explored through difference-in-difference approach. Results: Air quality of the 28 cities that adopted the regional cooperative pollution control policy improves significantly, thus indicating that this policy effectively solves the self-interest issue of local governments in pollution control, and residents' health expenditures consequently decrease. Conclusion: This study enriches the paradigm that analyzes the relationship between air pollution and residents' health expenditures and reveals the mechanism through which the regional cooperative pollution control reduces residents' health expenditures.